A STUDY ON AFFECT OF ADOPTING SILENT ELECTRIC VEHICLES ON PEDESTRIANS IN INDIA - Sharma, Subhashis Dhara (Digital Repository of Theses, 2023)
Vehicle powered by electric motors can be very quiet at low speeds, which can lead to new road safety issues. It becomes very hard for the pedestrians to recognize the presence of these vehicles due to the masking effect of background city noise and the co-existence of the internal combustion engine (ICE) vehicles running along with these new generation electric vehicles in turn becoming a potential cause for increasing road accidents. Many countries such as EU, USA, Japan, Korea and China have already brought in mandatory regulations to adopt AVAS in each EV. However, India is yet to bring such regulations. Further, the conditions in India in terms of various factors like population density, traffic density, road infrastructure, type of vehicles, city ambient noise etc. makes it different than other countries. The main intention of the studies presented in this paper was to study the ambient traffic noise at various different cities of India to benchmark and standardize the overall background noise in an as is condition thereby identifying the suitable AVAS sound dBA levels for each type of EV that can possibly ply on the busy Indian roads, so as to make it easy for the pedestrians which may include children, senior citizens and physically impaired people. The strategy incorporated a dual approach to narrow down to the exact solution along with the specifications that would be most appropriate for implementation of AVAS in India. First was to survey among common people, both, those owing an EV vehicle and general commuters and pedestrians to collate their experiences. Second was conducting field trials to analyze city ambient noise at various locations, minimum and maximum sound levels (dBA) in Indian context as per the vehicle type, their speeds and distance from the center line of the driving lane. Through the survey among the EV owners and the pedestrians it was clearly evident that both the groups do acclaim that an AVAS system will be quite helpful for them to avert potential accidents on road. As per the various experiments and tests conducted in this research, the normalized mean values of city ambient noise and traffic noise shows 84.6 dBA for highway and 84.3 dBA for city. Therefore, the EV must produce and emit minimum 2 to 3 dBA more than 84.6 dBA to be audible in a traffic. This minimum value should be emitted at low speed of 10kmph. The dBA should increase with increase in the speed level of the vehicle. It is not only the maximum sound level of AVAS which influence the potential detection by pedestrians. As part of the development of different AVAS sound design, the frequency content is very important. In the regulations for AVAS and minimum noise levels, it is recommended that the frequency content should be clearly specified. The regulations should have specific recommendations for minimum sound levels in the frequency spectra from 160 to 5000 Hz. Further, the frequency of the sound should resemble an ICE vehicle sound profile to make it more effective in audibility. In our experiment we have collected the frequency spectrum of ICE vehicle that shows the frequency is spread until 6500 Hz at an amplitude between 80 to 90 dBA. The AVAS sound for EV should also be designed in a similar fashion so as to improve its audibility distance.